Comparative dynamic analyses under HELB-induced jet impingement loads. (July 2019) - Kim, Seung Hyun; Kim, Tae-Jin; Goni, Md Nasimul; Chang, Yoon-Suk; Choi, Choengryul; Kim, Won Tae
Highlights: A dynamic numerical methodology was proposed for structural integrity assessment. Power spectral density data by jet impingement loads was converted under a HELB conditions. Assessment results by the proposed methodology were compared with those by implicit results. Abstract: While ANSI/ANS 58.2 has been widely adopted as a standard to protect nuclear power plants against effects of postulated piping rupture, there are still arguments in determination of dynamic fluid characteristics and application to structural integrity assessment. To solve non-conservativeness of jet impingement loads in the current standard, a numerical approach was proposed that is promising from computational fluid dynamics analyses standpoint but further elaboration seems necessary for FE (Finite Element) analyses due to its implicit feature. This study is to investigate appropriate dynamic FE methods and to quantify differences with the previous one under postulated high energy line break conditions. In detail, modal analyses were performed to assess the vibration characteristic of integrated component and structure as well as individual components. Subsequent vibration analyses were carried out by using the modal analyses results of the integrated full model and specific power spectral density data depend on the jet direction and target area. From the comparative study, the dynamic FE analyses provided approximately 47% higher von Mises stresses and 14% larger radial displacements than the implicit FE analyses at the critical location.